Helping young children believe by exposing Asmaul Husna through learning media - Zamzam, Rohimi; Usmiyatun, Usmiyatun; Suharsiwi, Suharsiwi; Olawale, Locus Son (CV. BImbingan Belajar Assyfa, 2023)
Asmaul Husna is a practical way to study faith. The magnificent name of Allah, Asmaul Husna, signifies his divine eloquence. The goal of learning Asmaul Husna is to teach youngsters faith. Youngsters are expected to adopt Asmaul Husna by learning Allah's beautiful names and characteristics. This project will be more accessible with learning media. This study seeks to determine the best methods for teaching young children Asmaul Husna. This study used a systematic review of relevant literature from 2013 to 2023 in respectable publications. Researchers methodically collected data from several current sources to learn about their topic. The data comes from Mendeley-indexed and validated books, theses, journals, and articles from credible websites. The search focused on